Detection and Molecular Characterization of Porcine Parvovirus 7 in Eastern Inner Mongolia Autonomous Region, China - Wen, Shubo; Song, Yang; Lv, Xiangyu; Meng, Xiaogang; Liu, Kai; Yang, Jingfeng; Diao, Fengying; He, Jinfei; Huo, Xiaowei; Chen, Zeliang; Zhai, Jingbo (Frontiers in Veterinary Science, 2022)
In the present study, we reported the identification of PPV7 for the first time in Inner Mongolia, China. Twenty-seven of ninety-four samples (28.72%) and five in eight pig farms were PPV7 positive. Further detection showed that the co-infection rate of PPV7 and PCV2 was 20.21% (19/94), and that of PCV3 was 9.59% (9/94). In addition, the positive rate of PPV7 in PCV2 or PCV3 positive samples was higher than that in PCV2 or PCV3 negative samples, supporting that PCV2 and PCV3 could act as co-factors of PPV7 to enhance PPV7 infection. In total, four PPV7 strains were sequenced and designated as NM-14, NM-19, NM-4, and NM-40. The amplified genome sequence of NM-14 and NM-40 were both 3999nt in length, while NM-19 and NM-4 were 3996nt with a three nucleotides deletion at the position of 3097-3099, resulting in an amino acid deletion in the Cap protein. Phylogenetic analysis based on the capsid aa sequences showed that 52 PPV7 strains were divided into two clades, and the four PPV7 strains in this study were all clustered in clade 1. The genome and capsid amino acid sequence of the four PPV7 strains identified in this study shared 80.0-96.9% and 86.1-100% similarity with that of 48 PPV7 reference strains randomly selected in NCBI, respectively. Simplot analysis revealed that NM-19 and NM-4 strains were probably produced by recombination of two PPV7 strains from China. The amino acid sequence alignment analysis of capsid revealed that the four PPV7 strains detected in Inner Mongolia had multiple amino acid mutations in the 6 B cell linear epitopes compared with the other reference strains, suggesting that the four PPV7 strains may have different characteristics in viral binding and immunogenicity. In summary, this paper reported the PPV7 prevalence and molecular genetic evolution characteristics in Inner Mongolia for the first time, which helps understand the molecular epidemic characteristics of PPV7.